Oszczędności a proces zabezpieczenia starości - Kubiak, Damian (Savings vs. the Process of Old Age Security, 2005)
Households play an important role in the, so called, circular movement. The income of households becomes divided into consumption type of expenditure and savings. They deliver capital to financial system, which is used for investments by enterprises. Households, while distributing their own income into consumption and savings, follow different reasons. The most important ones, apart from prudential, cash deals and portfolio type of reasons also include the old age security motive.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 180-187